Being an adult sibling of an individual with autism spectrum disorder may be a predictor of loneliness and depression – Preliminary findings from a cross-sectional study - Sipowicz, Kasper; Podlecka, Marlena; Mokros, Łukasz; Pietras, Tadeusz; Łuczyńska, Kamila (Frontiers in Psychology, 2022)
Background The aim of this study is to compare depression and loneliness among adult siblings of people on the autism spectrum, adult siblings of normotypic individuals, and adults raised alone (only child). In recent years, an increasing interest in the perspective of siblings of children diagnosed with autism has been observed, with studies among this population particularly concerned with the developmental trajectories of children and adolescents at “high risk” for ASD, rarely focusing on their mental well-being. Methods The respondents filled out: the survey on sociodemographic data designed by the authors, Beck Depression Inventory II (BDI, measure of depression), and De Jong Gierveld Loneliness Scale (DJGLS, assessment of loneliness). Results A rise in BDI and an increase in the DJGLS score were predicted by having a sibling diagnosed with ASD. Those effects were independent of subjects’ sex, educational status, place of residence, or a number of siblings. Conclusions The results underline a fundamental need for the development of mental hygiene programs for families where children with autism spectrum are accompanied by healthy siblings.